Analisis Kinerja Pegawai Ditinjau dari Kepemimpinan, Whistleblowing System dan Komitmen Organisasi - Nawan Endro Santoso; Abu Talkah; Ahsin Daroini (Universitas Islam Kadiri, 2020)
Employee performance at the Tulungagung Tax Office is expected to be of good value whose impact can increase state tax revenues as the main source of financing. This study aims to determine significantly the influence of leadership style, whistleblowing system and organizational commitment to employee performance at the Tulungagung Tax Office. This research uses quantitative research methods with a population of 90 employees as respondents. The research variables consist of independent variables, namely leadership style, whistleblowing system and organizational commitment and the dependent variable is employee performance. Data collection using a questionnaire that was measured by a 5 level linkert scale. The analysis tool uses multiple linear regression. The results showed that there was an influence both partially and simultaneously the leadership style of the whistleblowing system and organizational commitment on employee performance.